ANALYSIS OF VARIANCE SPERMOGRAM INDICATORS OF MEN DIFFERENT AGE GROUPS WITH ASTENOZOOSPERMIA, TERATOZOOSPERMIA AND AZOOSPERMIA - Tarnovska, Antonina; Heneha, Anastasiia (Scientific Journal of Polonia University, 2024)
In recent decades, a decline in male fertility due to deterioration in sperm quality hasbeen noted around the world. This is probably explained by the tendency to increase the diseasesof the male genital organs and, as a result, the increase in the percentage of male infertility.In addition, there is a deterioration of the quantitative and qualitative indicators of spermogramsin practically healthy men. The average number of sperm in the ejaculate of a healthy man hashalved over the past 50 years, and the average volume of ejaculate has decreased by one third. Itis known that the multicomponent composition of the internal male genital organs is in constantrestructuring due to age changes, functional activity and the influence of various factors. That iswhy it is important to take into account both physiological and age-related changes in a man’sability to conceive.Diagnosis of male infertility includes clinical research methods and methods of laboratory-instrumental examination. Among the latter, the most important for finding out the functionalstate of the gonads and the fertilizing ability of sperm is the study of ejaculate. The object ofour research was spermograms obtained during the examination of patients at the "AlternativeClinic" reproductive medicine clinic.The purpose of the work was using biometric analysis to the different indicators of menspermograms of younger, middle and older age groups with normozoospermia (N), asthenozoospermia(AZS), teratozoospermia (T) and azoospermia (A). The task of the research wasto analyze the main indicators of spermograms of men of different age groups in normal andpathological conditions, to conduct a one-factor and two-factor variance analysis of the influenceof the studied diseases and age factor.After analyzing the main indicators of spermograms of men of younger, middle andolder age groups with asthenozoospermia, azoospermia, and teratozoospermia, it was establishedthat the indicators that undergo the greatest deviations in the studied diseases are themobility of spermatozoa according to categories A and B, the morphology of spermatozoa, theFarris fertility index, and the activity of spermatozoa.After conducting a one-factor variance analysis, we established that the share of theinfluence of the studied diseases on the overall variability of such indicators of spermograms asthe mobility of spermatozoa according to category A and B and the morphology of spermatozoain the spermograms of men of the studied age groups is within 63–98% of the total contribution(younger age group), 60–96% (middle age group) and 75–96% (older age group). The shareof influence of unaccounted factors is within 2–40% of the total contribution. The share of theinfluence of the studied diseases in the overall variability of such indicators as the Farris index and sperm activity in the spermograms of men of all studied groups is significantly reducedand is within 22–44% of the total contribution. Instead, the influence of unaccounted factors(56–78% of the total contribution) is growing significantly. This may indicate the presence ofconcomitant diseases and other pathologies in the men who took part in the research.After conducting a two-factor variance analysis, we established that the shares of theinfluence of the studied diseases on the overall variability of such indicators of spermogramsas motility of spermatozoa according to category A and B, morphology of spermatozoa, Farrisfertility index and activity of spermatozoa are decisive and are within the range of 90.7–99.9%of the total contribution, the share of the influence of the age factor on the variability of spermogramindicators of men of different age groups is insignificant.